Effect of Tissue Factor Pathway Inhibitor (TFPI) in the HEPTEST® Assay and in an Amidolytic Anti Factor Xa Assay for LMW Heparin - Kristensen, Hanne I; Østergaard, Per B; Nordfang, Ole; Abildgaard, Ulrich; Lindahl, Anne Karin (Thrombosis and Haemostasis, 1992)
Both the HEPTEST® and amidolytic anti factor Xa assays are currently being used for heparin activity detection in plasma from patients receiving standard heparin or low molecular weight heparin (LMWH). In this study we have investigated the influence of recombinant and endogenous Tissue Factor Pathway Inhibitor (TFPI) on these assays. The HEPTEST® determinations were performed on an ACL 300 R Clottimer using the APTT program which resulted in a longer incubation time with factor Xa than recommended by the manufacturer. rTFPI added to plasma prolonged the HEPTEST® clotting time markedly, but had only a little effect in the amidolytic assay. Antibodies against TFPI (anti-TFPI) abolished these effects. The effect of adding rTFPI and Logiparin® was additive. When anti-TFPI IgG was added to samples of normal plasma, a statistically significant shortening of the HEPTEST® clotting time was seen. When anti-TFPI was added to plasma samples from volunteers who had received Logiparin® by subcutaneous or intravenous injection, then the HEPTEST® clotting time was shortened considerably. For some samples the clotting time was halved. These experiments show that the HEPTEST® clotting time is prolonged not only by heparin-antithrombin III, but also by TFPI released by heparin injection.